Antioxidant and Anticholinesterase Properties of the Aqueous Extract of Balanites aegyptiaca L. Delile Fruit Pulp on Monosodium Glutamate-Induced Excitotoxicity in Swiss Mice. (11th April 2022) - Parfait, Bouvourné; Galba Jean, Beppe; Roger, Ponka; Hervé Hervé, Ngatanko Abaissou; Balbine, Kamleu Kwingwa; Guillaume, Camdi Woumitna; Simon Desire, Guedang Nyayi; Linda, Damo Kamda Jorelle; Léa Blondelle, Kenko Djoumessie; Germain, Sotoing Taiwe
Abstract : Balanites aegyptiaca L. Delile ( B . aegyptiaca ) is used in traditional medicine for the treatment of memory impairment. This work aims to evaluate the antioxidant and anticholinesterase potential of BA fruit pulp extract on excitotoxicity induced by monosodium glutamate (MSG). MSG was administered 30 minutes after treatment with B . aegyptiaca aqueous fruit pulp extract (50, 125, 250, and 500 mg/kg) and vitamin C (100 mg/kg) for 30 days. The negative control group received only MSG, while the control group was given distilled water daily. Behavioral tests parameters (using the novel object recognition, Y-maze, and Barnes maze tests), oxidative stress biomarkers (malondialdehyde, superoxide dismutase, and catalase), nitric oxide, and acetylcholinesterase activity and hippocampal architecture were evaluated. Results obtained revealed that different doses of B . aegyptiaca significantly reversed the deleterious effect of MSG on memory. This was displayed by a significant (p < 0.05 ) increment in the percentage of spontaneous alternation in the Y-maze test and a significant (p < 0.001 ) increase in discrimination index in novel object recognition observed with 500 mg/kg extract dose. Moreover, the extract (250 and 500 mg/kg doses) significantly (p < 0.001 ) increased direct search strategy and significantly decreased (p < 0.01 ) the time taken to find the target hole in the Barnes maze. A modulation of hyperactivity was observed after administration of all extract doses compared to the negative control group in the open arena. Furthermore, the highest dose of the extract caused a significant (p < 0.001 ) improvement in antioxidant enzymes activity, associated with a significant (p < 0.001 ) decrement in nitric oxide and malondialdehyde concentrations and a significant (p < 0.01 ) decrease in acetylcholinesterase activity. Treatment with the extract also restored normal hippocampal cell architecture. B . aegyptiaca fruit pulp extract could thus confer neuroprotection through its antioxidant and anticholinesterase potential.